Tuning the Electrical Conductivity of Bacterial Cellulose Membranes by Multi-Walled Carbon Nanotube Insertion as Bio-Nanocomposite Conductive Materials - Joris, Shielda Natalia; Onggo, Djulia (Jurnal Kimia Riset, 2025)
Bacterial cellulose (BC) obtained from nata-de-coco represents a sustainable biopolymer that offers broad potential as a platform for functional material development. In this work, the electrical performance of BC was improved through the incorporation of multi-walled carbon nanotubes (MWCNTs), which were dispersed in a cetyltrimethylammonium bromide (CTAB) solution prepared at a 1:1 mass ratio. The resulting composite membranes were examined using four-point probe measurements, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The electrical conductivity increased from 0.2 S cm⁻¹ to 1.2 S cm⁻¹ as immersion time was extended, reaching an optimum after six days, which was attributed to better nanotube dispersion and alignment inside the cellulose fibril matrix. SEM and thermal analyses confirmed the gradual integration of MWCNTs into the BC framework. The findings demonstrate that adjusting the insertion duration of nanotubes can effectively modulate the electrical properties of BC membranes, supporting their potential as green bio-nanocomposites for emerging energy and electronic technologies.